2016
DOI: 10.18632/oncotarget.11455
|View full text |Cite
|
Sign up to set email alerts
|

Activation of HERV-K Env protein is essential for tumorigenesis and metastasis of breast cancer cells

Abstract: Human endogenous retrovirus type K (HERV-K) Env protein was previously demonstrated to be overexpressed in human breast cancer (BC) cells and tissues. However, the molecular pathways driving the specific alterations are unknown. We now show that knockdown of its expression with an shRNA (shRNAenv) blocked BC cell proliferation, migration, and invasion. shRNAenv transduction also attenuated the ability of BC cells to form tumors, and notably prevented metastasis. Mechanistically, downregulation of HERV-K blocke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
111
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(132 citation statements)
references
References 33 publications
8
111
0
Order By: Relevance
“…KRAS expression led to activation of JNK in pancreatic cancer cell lines (71). HERV-K control of RAS expression has been reported by us in breast cancer (41,42), and our results in the current study using KRAS mutant Panc-1 cells suggest that HERV-K may induce JNK activation in PCs with KRAS mutation.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…KRAS expression led to activation of JNK in pancreatic cancer cell lines (71). HERV-K control of RAS expression has been reported by us in breast cancer (41,42), and our results in the current study using KRAS mutant Panc-1 cells suggest that HERV-K may induce JNK activation in PCs with KRAS mutation.…”
Section: Discussionsupporting
confidence: 81%
“…Although HERV-K is the most complete and biologically active family of HERVs, the precise mechanism leading to abnormal HERV gene expression has yet to be clearly understood. Our results below and recent publications [ours (42) (39,41) and others (43)] provide strong evidence that abnormal expression of HERV-K triggers pathological processes leading to cancer onset, and also contributes to the morphological and functional cellular modifications implicated in cancer progression (29). HERV-K can express two accessory viral proteins, Rec and NP9, which are believed to have oncogenic potential (44).…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…A number of different transcription factors have been associated with EMT, and this generic term in fact covers several processes that can occur in different circumstances, either in normal development or in the course of disease [30]. Previous studies had already hinted at oncogenic properties for HERV-K Env, but it had only been shown that this Env protein can alter the phenotype of pre-transformed, cancer-derived cell lines [2325] whereas we demonstrate here that it can also direct non-malignant cells in the path towards transformation. Given the change of the EMT markers and cell motility observed, it is likely that HERV-K Env expression by a tumour or a pre-tumour could also trigger further changes and favour metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…The upregulated level of Np9 protein which is coded by type 1 HERV-K promoted the growth of leukemia cells in vitro and in vivo by not only activating ERK, AKT, and Notch1 pathways but also upregulating β -catenin essential for survival of leukemia stem cells [44]. In human breast cancer, the overexpressed HERV-K specifically increases Ras-induced ERK activation, which suggests that the oncogenic activity of Ras protein is propagated by activation of HERV-K Env protein [45]. While the role which this upregulated HERV-K would play in HCC and the underlying signaling pathways are still unknown, we assume that HERV-K could be related to the transformation and tumorigenesis of HCC through Ras signaling pathways due to the detection of activated Ras/Raf/MAPK pathway in HCC [46].…”
Section: Discussionmentioning
confidence: 99%